2021
DOI: 10.3390/cells10020448
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of microRNAs in inducing Drug Resistance in Patients with Multiple Myeloma

Abstract: The prognosis for newly diagnosed subjects with multiple myeloma (MM) has significantly progressed in recent years. However, most MM patients relapse and after several salvage therapies, the onset of multidrug resistance provokes the occurrence of a refractory disease. A continuous and bidirectional exchange of information takes place between the cells of the microenvironment and neoplastic cells to solicit the demands of cancer cells. Among the molecules serving as messengers, there are microRNAs (miRNA), a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 144 publications
0
14
0
Order By: Relevance
“…Moreover, resistance to tumor treatment is still a critical problem, causing relapse and decreased overall survival. Several mechanisms that promote chemoresistance have been reported [92,93], and it is recognized that aggressive aptitudes and chemoresistance are correlated to the augmented communication function in tumor cells, and TNTs could have an effect in the onset of chemoresistance. Mitochondrial transfer may induce chemoresistance through different systems, comprising the inhibition of programmed cell death, the decreased production of ROS, and the increased salvaging of cells with altered mitochondria [94].…”
Section: Tnts and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, resistance to tumor treatment is still a critical problem, causing relapse and decreased overall survival. Several mechanisms that promote chemoresistance have been reported [92,93], and it is recognized that aggressive aptitudes and chemoresistance are correlated to the augmented communication function in tumor cells, and TNTs could have an effect in the onset of chemoresistance. Mitochondrial transfer may induce chemoresistance through different systems, comprising the inhibition of programmed cell death, the decreased production of ROS, and the increased salvaging of cells with altered mitochondria [94].…”
Section: Tnts and Cancermentioning
confidence: 99%
“…Furthermore, it was reported that TNT signaling from MSCs to ALL cells might also provoke the chemoresistance of leukemic cells (Figure 4). For example, TNTs have been reported to transfer drug efflux pumps, such as P-glycoproteins, toward tumor cells [92].…”
Section: Tnts and Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%
“…miRNAs can function as oncogenic or suppressors of tumors. It has been reported that miRNAs may control the drug response of MM cells through regula-tion of the apoptotic or proliferative pathways, which include p53 [46], which is a transcription factor that can stimulate tumor suppressor miRNAs or even inhibit some on-comiRNAs [47]. The miRNAs activated by p53 have been reported to affect the antiapoptotic genes, thereby enhancing the tumor suppressor activity of p53 [47].…”
Section: Involvement Of Mirnas and Its Dysregulations And Outcomementioning
confidence: 99%
“…In spite of the progress with antimyeloma therapy, the occurrence of chemoresistance is still the main reason for MM relapse [ 78 ]. The conditions causing chemoresistance are composite mechanisms, including increased drug efflux pumps efficacy, reduced drug levels, modification in DNA repair, changes in growth and programmed cell death [ 79 ], and all types of ncRNAs appear to have a relevant effect on the occurrence of MM drug resistance [ 80 ].…”
Section: Circrnas and Multiple Myelomamentioning
confidence: 99%